• sartalon@lemmy.world
    link
    fedilink
    arrow-up
    2
    ·
    4 hours ago

    X^3 = x•x•x

    X^2 = x•x

    X^1 = x

    X^0 = 1

    X^-1 = 1/x

    X^-2 = 1/(x•x)

    X^-3 = 1/(x•x•x)

    When the exponent is between -1 and 1, it becomes a root function:

    X^(1/2) = sqrt(x)

    X^(1/3) = cubic root(x)

    X^-(1/2) = 1/(sqrt(x))

    X^-(1/3) = 1/(cubic root(x))

    • JPAKx4@lemmy.blahaj.zone
      link
      fedilink
      arrow-up
      2
      ·
      3 hours ago

      Oh I misunderstood the original comment, the teacher said it wasn’t the same, but it is the same. My understanding is that sqrt(x) = x^1/2